Effects of rate-dependent behavior of sandstone on performance of gas storage in aquifer. (September 2022) - Wang, Zhechao; Li, Wei; Qiao, Liping; Guo, Jiafan; Liu, Yuqin
Abstract: Strain rate is one of the main factors affecting the properties of rock masses. The effect of strain rate on performance of gas storage in aquifer is investigated combining laboratory tests and constitutive and numerical models. Triaxial tests on sandstone specimens at different strain rates were carried out and the effect of strain rate on mechanical properties of sandstones was investigated. The results showed that the peak strength, axial strain, elastic modulus, Poisson's ratio, cohesion and internal friction angle of sandstone specimens increased with strain rate. In addition, the elastic–viscoplastic properties of sandstones have been analyzed. It indicated that the deflection angle in the viscoplastic flow direction was increased with strain rate and viscoplastic volumetric strain grew faster than the viscoplastic deviator strain. A rate-dependent constitutive model was adopted and a method for solving the parameters of the constitutive model was determined based on test data. For the constitutive model, the elastic part is a linear elastic model, the plastic part is a linear Drucker–Prager model, and the viscous part is a power law constitutive function. The model and methodology for parameter determination were validated against the test data of sandstones. The results showed that the model selected in this study can well describe effects of strain rate on the mechanical properties of sandstones. The model and method have been applied in gas injection and production capacity assessment of a gas storage in aquifer and the strain rate of the formation was determined by gas injection pressure and time indirectly in simulation. The simulation results showed that the gas injection and production rate of gas storage in aquifer will increase significantly with the strain rate of formation in the same gas injection pressure or time. It also indicated that the gas production capacity will be greatly improved with the strain rate of formation. Highlights: Effect of strain rate on mechanical properties of sandstones was investigated. Mechanical and deformation parameters were increased with strain rate. A method for solving the parameters of the rate-dependent constitutive model was proposed. Gas production capacity of gas storage in aquifer increase significantly with the strain rate of formation.